Studi Literatur : Analisis Model Pembelajaran Discovery Learning dalam Meningkatkan Berpikir Kritis Siswa pada Pembelajaran Fisika - Angellika C Simanjuntak; Novry Hiskia Hamonangan Simanullang; Putri Hanna Mariana Limbong; Rima Ariani (Jurnal Bintang Pendidikan Indonesia, 2025)
This research aims to 1) describe the implementation of learning, 2) students' critical thinking skills, 3) students' responses to the scientifically oriented discovery learning model. This research is a meta-analysis research that describes the effect size of educational research regarding the influence of the Discovery Learning model in Physics learning, especially on students' critical thinking. The analysis method is research carried out by collecting and summarizing research data from the results of previous research. This research applies meta-analysis techniques, namely referring to 20 journals with a distribution range of 2015 - 2023. This research is expected to be able to determine the feasibility of the Discovery Learning learning model in physics subjects with the factors of lesson topics and tools used in learning being the focus point. regarding students' critical thinking abilities.